THE ANALYSIS OF TPACK IMPLEMENTATION IN THE RUANG GURU ENGLISH COURSE - Krisna Ismawati; Helta Anggia (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2021)
The objective of this research was to describe the implementation of TPACK framework in the Ruangguru as English online course. Descriptive qualitative was used to conduct this research. We used observation to gather our data by observing the features and the learning process in the Ruangguru including what contents are inside, what technology or media used, what methods used to deliver the material and how they related one to each other. Based on the entire result, we found that the implementation of TPACK framework in the Ruangguru looks quite appropriate based on the existing principles. Both the observation result and the questionnaire responses showed the existence of the TPACK principles in the Ruangguru even though there are some categories that still did not seem appropriate, such as the single use of lecturing method in each lesson, and the absence of practice skills. However, it was only a small part that did not match one among many TPACK principles implemented in the Ruangguru. Overall, TPACK was implemented in the Ruangguru, but there is still a big room for improvement in the future due to the frequent updates on the system and increasing additional new features.